2007
DOI: 10.1016/j.immuni.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,3,4,5-Tetrakisphosphate Negatively Regulates Phosphatidylinositol-3,4,5- Trisphosphate Signaling in Neutrophils

Abstract: Many neutrophil functions are regulated by phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P3) that mediates protein membrane translocation via binding to pleckstrin homolog (PH) domains within target proteins. Here we show that inositol 1,3,4,5-tetrakisphosphate (Ins(1,3,4,5)P4), a cytosolic small molecule, bound the same PH domain of target proteins and competed for binding to PtdIns(3,4,5)P3. In neutrophils, chemoattractant stimulation triggered rapid elevation in Ins(1,3,4,5)P4 concentration. Deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 79 publications
1
119
0
Order By: Relevance
“…9,10 In neutrophils, disruption of InsP3KB does not affect the overall calcium signaling in the presence of extracellular calcium. 16 However, more detailed investigation revealed a much decreased calcium release from intracellular store and an enhanced calcium influx through store-operated calcium channels in InsP3KB null neutrophils stimulated with chemokines. The reduction of calcium release from intracellular store appears to be a result of calcium depletion from the store (Jia Y and Luo HR, unpublished data) (Fig.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
See 4 more Smart Citations
“…9,10 In neutrophils, disruption of InsP3KB does not affect the overall calcium signaling in the presence of extracellular calcium. 16 However, more detailed investigation revealed a much decreased calcium release from intracellular store and an enhanced calcium influx through store-operated calcium channels in InsP3KB null neutrophils stimulated with chemokines. The reduction of calcium release from intracellular store appears to be a result of calcium depletion from the store (Jia Y and Luo HR, unpublished data) (Fig.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…14,15 Recently, we demonstrated that two inositol phosphates, InsP7 and Ins(1,3,4,5)P4, compete for Akt-PH domain binding with PtdIns(3,4,5)P3 both in vitro and in vivo, providing another level of regulation for Akt membrane translocation and activation. 16,17 In hematopoietic progenitor cells, depletion of Ins(1,3,4,5)P4 by disrupting InsP3KB gene enhances membrane translocation of PtdIns(3,4,5)P3 specific PH domain, thus augments the PtdIns(3,4,5)P3 downstream signals such as Akt. As a result, the phosphorylation of cell cycle inhibitory protein p21 cip1 , a target of Akt, is enhanced, leading to diminished cell cycle inhibitory effect of p21 cip1 .…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
See 3 more Smart Citations